Pinoy rock revival shedding light on classic pinoy rock to encourage Filipino teenagers to value local music - Jarantilla, Maxine K.
The decline of record sales and the constant popularity of foreign music, aside from piracy, are only manifestations of deeper issues that the music industry faces today. The real problem lies in how Filipino music fans, particularly teenagers, perceive local music. Foreign music is too appealing that most music fans favor it over local music. The researcher has discovered that in order to promote interest in pinoy rock, the genre must be marketed as if it were a new genre. Most of the younger generations of music fans are familiar with bands like Eraserheads and Rivermaya, but the more classic pinor rock bands like Juan Dela Cruz and Sampaguita are in danger of being unrecognizable. The teenagers may find some of the songs familiar, but they are not able to truly appreciate the music due to the fact that they are unaware of the artists. By integrating the genre into modern music channels, local gig productions in particular, Classic Pinor Rock may gain more exposure and playing the songs frequently for younger audiences can elicit appreciation from them. The more the audience accpets their culture, the more they can be proud of it.